Secondary electron emission from multi-layered TiN/Al2O3 transmission dynodes. (15th July 2021) - Chan, H.W.; Prodanović, V.; Theulings, A.M.M.G.; Hagen, C.W.; Sarro, P.M.; Graaf, H.v.d.
Abstract: The (secondary) electron emission from multilayered Al2 O3 /TiN membranes has been investigated with a hemispherical collector system in a scanning electron microscope for electrons with energies between 0.3 and 10  keV. These ultra-thin membranes are designed to function as transmission dynodes in novel vacuum electron multipliers. Two different types, a bi-layer and a tri-layer, have been manufactured by means of atomic-layer deposition (ALD) of aluminum oxide and sputtering of titanium nitride. The reflection and transmission electron yield ( σ R, σ T ) have been measured for both types of membranes. In comparison, the tri-layer membranes outperformed the bi-layer membranes in terms of transmission electron yield for films with the same effective thickness. The highest transmission electron yield was measured on an Al2 O3 /TiN/Al2 O3 film with layer thicknesses of 5/2.5/5  nm, which had a maximum transmission electron yield σ T max ( E 0 ) of 3.1 (1.55  keV). Furthermore, the bi-layer membranes have been investigated more in-depth by performing an additional measurement using a positive sample bias to separate the transmitted fraction η T and the transmission secondary electron yield δ T . The transmitted fraction was used to determine the transmission parameter p, which characterizes the interaction of primary electrons (PEs) in thin films. The transmission secondary electron yield was used to compare the energy transfer of PEs in films with different thicknesses.